2022
DOI: 10.1097/prs.0000000000008789
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Plastic Surgery Authorship: A 14-Year Analysis of 2688 Articles Published in Plastic and Reconstructive Surgery

Abstract: Background: Publication in peer-reviewed journals is a duty and privilege. It is essential to the advancement of evidence-based medicine and often used as a proxy for academic achievement, contributing to decisions around promotion in academia. Within plastic surgery, authors have historically been male surgeons affiliated with academic institutions, lacking representation of women, private practice, medical students, and international collaboration. This study analyzes differences in authors' gender, practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…[27][28][29] In plastic surgery specifically, gender-in-authorship disparities seem to be decreasing but remain heavily biased toward male-authored publications. 30,31 This observation is unsurprising considering that plastic surgery has been maledominated since its inception, although the percentage of women entering the field has consistently increased. [32][33][34] The h index was thought to be an objective measure of scholarly success, but a single metric is unlikely to provide an objective account of research productivity, especially if it is biased and does not fully represent the quality or value of the publication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] In plastic surgery specifically, gender-in-authorship disparities seem to be decreasing but remain heavily biased toward male-authored publications. 30,31 This observation is unsurprising considering that plastic surgery has been maledominated since its inception, although the percentage of women entering the field has consistently increased. [32][33][34] The h index was thought to be an objective measure of scholarly success, but a single metric is unlikely to provide an objective account of research productivity, especially if it is biased and does not fully represent the quality or value of the publication.…”
Section: Discussionmentioning
confidence: 99%
“…In general, women authors have fewer publications and citations than their male colleagues, and in some fields, such as neuroscience and physics, manuscripts authored by women are cited by men far less frequently than publications authored by men 27–29 . In plastic surgery specifically, gender-in-authorship disparities seem to be decreasing but remain heavily biased toward male-authored publications 30,31 . This observation is unsurprising considering that plastic surgery has been male-dominated since its inception, although the percentage of women entering the field has consistently increased 32–34 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a prior study found no evidence of sex bias in the selection of integrated plastic surgery residents based on the sex of PCs and directors; however, they did not examine the effect of sex composition on the institution's faculty. 7 It has also been demonstrated 14 that a growing number of females are contributing to the plastic surgery literature. These findings, coupled with the results of our study, provide encouraging evidence of the narrowing sex gap and steadily improving sex equity within plastic surgery.…”
Section: Sex Diversitymentioning
confidence: 99%
“…30 The barriers to execution of high LOE research are many, including the ethical concerns associated with use of a surgical control group or placebo, conflict of study design with informed consent, low volume of rare procedures or diseases, and the hurdles of establishing data-sharing infrastructure, to name a few. The low-volume concern can be addressed through multi-institutional studies, which are becoming increasingly popular 24,31 ; however, this often introduces variability in surgical technique and postoperative care that may confound findings. Nevertheless, this interinstitutional variation in medical and surgical management may produce more generalizable conclusions, yet another strength of multicenter research.…”
Section: Prs Global Open • 2022mentioning
confidence: 99%
“…Plastic surgery research has become an increasingly global enterprise over the past decade. [22][23][24] Nevertheless, the desired reliability and granularity of variables from online sources guided our methodology toward exclusion of international authors. This proved helpful in standardizing the sample due to key differences in fellowship requirements, board certification, and lack of NIH funding among non-US-based plastic surgeons.…”
Section: Prs Global Open • 2022mentioning
confidence: 99%